Management of Facilities and Infrastructure in Improving the Quality of Learning at Pusri Palembang Elementary School - Vastha Vusvitha (LPPM Institut Studi Islam Sunan Doe, 2023)
The purpose of this study was to determine the Management of Facilities and Infrastructure in Improving the Quality of Learning at SD PUSRI Palembang. This research is motivated by adequate facilities and infrastructure to support learning activities and can be said to be an example for other schools. This type of research is qualitative with a descriptive approach. The object of this study is the management of facilities and infrastructure at SD PUSRI Palembang, while the subjects of the study are the principal, teachers and education staff. Data collection techniques used are observation, interviews and documentation. Data analysis techniques used data reduction, data presentation and conclusion. The results of the study are that there are six management of infrastructure facilities at SD PUSRI Palembang, namely planning of infrastructure facilities, procurement of infrastructure facilities, determination and implementation of infrastructure facilities, control of infrastructure facilities, maintenance of infrastructure facilities and removal of infrastructure facilities, all of which are going well in accordance with the objectives to be achieved. In improving the quality of learning it focuses on good management through the planning process so that it gets good results and can be used as an example for other schools.